Broadband Polarization Manipulation Based on W-Shaped Metasurface - Xu, Guangyuan; Gao, Lei; Chen, Yongqiang; Ding, Yaqiong; Wang, Jun; Fang, Yu; Wu, Xingzhi; Sun, Yong (Frontiers in Materials, 2022)
We present a metasurface consisting of W-shaped resonators to realize broadband reflective linear and circular polarization conversions. We find that the cross polarization conversion ratio for normal incidence is over 0.95 from 9.2 GHz to 18.7 GHz, covering 68.1% of the central frequency. We also show that, the conversion performance is almost insensitive to the angle of incident waves. Furthermore, by simply adjusting the geometrical parameters of the W-shaped metasurface, the broadband circular polarization conversion is also achieved. We emphasize that the bandwidth of axis ratio less than 3.0 dB covers from 10.1 GHz to 17.7 GHz, equivalent to 54.7% relative bandwidth. Due to these broadband and high-efficiency polarization conversion features, our proposal may have a wide application prospect.